Buying behaviour and decision-making criteria of Base of the Pyramid consumers : the influence of packaging on fast moving consumer goods customers’ brand experience - Chimhanzi, Jackie (University of Pretoria, 2013)
Dissertation (MBA)--University of Pretoria, 2010.